2020
DOI: 10.1097/md.0000000000018644
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of Ki-67/MIB-1 in meningioma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 75 publications
3
53
0
4
Order By: Relevance
“…Negative predictors for tumor progression in meningioma include male sex, young age, low Karnofsky performance status, high WHO grade, high mitotic rate, subtotal resection, and involvement of the optic nerve [ 24 ]. A high MIB-1 labeling index is strongly associated with shorter progression-free survival in meningioma and positively correlates with the meningioma grade [ 13 , 25 , 26 ]. In a typically elective setting, it is particularly important that patients and their relatives are provided with most comprehensive consultation possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative predictors for tumor progression in meningioma include male sex, young age, low Karnofsky performance status, high WHO grade, high mitotic rate, subtotal resection, and involvement of the optic nerve [ 24 ]. A high MIB-1 labeling index is strongly associated with shorter progression-free survival in meningioma and positively correlates with the meningioma grade [ 13 , 25 , 26 ]. In a typically elective setting, it is particularly important that patients and their relatives are provided with most comprehensive consultation possible.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the detection of this antigen is a feasible technique in order to determine the growing fraction of a neoplastic cell tissue sample [ 7 , 8 , 9 ]. Moreover, numerous studies and a recent meta-analysis have shown that the Ki-67/MIB-1 labeling index is an independent predictor of progression-free survival (PFS) in meningiomas [ 10 , 11 , 12 , 13 ]. To achieve the best possible long-term outcome with regard to tumor recurrence, appropriate preoperative assessment, effective communication about the aims of surgery, and function-preserving surgery are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Even in modern cohorts with extended follow-up, Simpson Grade 1 resections more than double the chance of progression-free survival, especially in high-grade meningiomas ( 19 ). In addition to Simpson grade, higher initial tumor size and MIB-1/Ki-67 indices, as well as presence of necrosis may decrease progression- and recurrence-free survival ( 19 22 ).…”
Section: Prognostic Factors For Meningiomasmentioning
confidence: 99%
“…Ki-67 has been widely used in studies of the proliferative potential of meningiomas ( 22 ). A recent meta-analysis by Liu et al indicated a significant adverse prognostic value of a high Ki-67 expression level in the prognosis of meningiomas, and 4% was recommended as the appropriate cutoff value ( 47 ). Of their 43 included studies (comprising 5012 patients), only seven specifically targeted WHO grade II meningiomas and evaluated the prognostic value of Ki-67 expression in tumor recurrence ( 11 14 , 48 50 ).…”
Section: Discussionmentioning
confidence: 99%